Literature Review: Pemberian Konseling Keluarga Berencana terhadap Pengambilan Keputusan Akseptor Memilih Keluarga Berencana Pasca Persalinan - Devy Silvia; Febi Ratnasari; Lastri Mei Winarni (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
One of the causes of the relatively fast population growth rate is because the average fertility rate or Total Fertility Rate (TFR) increases. The increase in TFR is also due to an increase in unmet need for family planning, especially in postpartum mothers. So that if the increase in TFR is not overcome by family planning programs, especially post-delivery family planning, there will be four too (4T), namely too young, too old, too many children, too often pregnancy is the cause of increased maternal and infant mortality. Objective: To review articles that discuss the provision of family planning to post-partum mothers. Methods: The author uses a literature review. In searching for several articles, this literature uses the Google Scholar, Pubmed and Scientific Director databases with inclusion criteria, namely using Indonesian and English, respondents are pregnant women in the third trimester or postpartum mothers. The articles obtained are from primary sources with a time span of 5 years (2017-2021). Results: Based on the literature review, it was found that the coverage of family planning acceptors in choosing post-delivery family planning was more likely to choose Long-Term Contraception Methods (LTCM) such as implants and IUDs, so it can be concluded that there is a significant relationship in the provision of post-delivery family planning counseling when pregnant women are in the third trimester. and at the time of postpartum to choose and decide on postnatal family planning.